Foraster de fora: entre la gran literatura i l'humor escèptic. - BOU, ENRIC (Scripta)
This article is a critical approach to Manuel Foraster's (1949-2016) trilogy «Foraster de for a»: Factures pagades (Tusquets 2012), Lisboa direcció París (Tusquets, 2014) i Sabadell Grand Central, Nova York Rambla (Tusquets, 2016). Based on a redrafting of the author's life experience, the trilogy is based on the concept of travel and mobility. The author followed in the footsteps of Eduard Toda's trip to Egypt, whose diary Forater studied and edited. He was also a lecturer at the universities of Bordeaux and Naples. He was a singular character. The singularity was accentuated by surnames that conditioned his destiny: Foraster and Giravent. He had the good fortune of an almost oxymoronic name. Readings and writing defined and guided him in life. Foraster (foreigner), as a «native or native of a town or country different from the one where he is» he had to explore the world. And he did address «to all winds». With infinite curiosity. And with a large dose of humor, the «supersensitive», which Carner defined in reference to Francesc Trabal. The result is a trilogy of novels that straddle the campus novel genre so prevalent in the Anglo-Saxon world.